Finite element approximation of a Cahn-Hilliard-Navier-Stokes system - Kay, D; Styles, V; Welford, R (2008)
We consider a semi-discrete and a practical fully discrete finite element approximation of a Cahn-Hilliard-Navier-Stokes system. This system arises in the modelling of multiphase fluid systems. We show order h error estimate between the solution of the system and the solution of the semi-discrete approximation. We also show the convergence of the fully discrete approximation. Finally, we present an efficient implementation of the fully discrete scheme together with some numerical simulations. © European Mathematical Society 2008.